What students’ narratives show about the development of autonomy in their initial teacher training (Praxis Educativa, 2014)
In the European context, a group of integration policies, included in the process of Bolonia, introduced lines of action as an opportunity to revise professional training and transform higher teaching through a process of development of autonomy, meaningful participation and availability for personal development through life. From this perspective, this paper analyzes the development of autonomy in students at initial teacher training, using their narratives and keeping in mind the different training situations in which they are immersed. These narratives revealed a declared autonomy when students speak about the implications of the process of Bolonia and their own learning. On the other hand, through narration in its tridimentional perspective, acquired dimensions of autonomy are revealed, which are built in their biographic, relational and institutional trajectories, even before starting the initial training.
Keywords: narratives; profesional training; autonomy; trajectory; higher education